Effect of Heat-Inactivated Compound Probiotics on Growth Performance, Plasma Biochemical Indices, and Cecal Microbiome in Yellow-Feathered Broilers - Zhu, Cui; Gong, Li; Huang, Kaiyong; Li, Fangjun; Tong, Diqing; Zhang, Huihua (Frontiers in microbiology, 2020)
This study was carried out to investigate the effect of heat-inactivated compound probiotics on growth performance, plasma biochemical indices, and gut microbiota composition and functions in yellow-feathered broilers. A total of 360 1-day-old broilers were randomly divided into 3 groups, including a basal diet as negative control group (PC), basal diet plus antibiotics with 250 mg/kg calcium oxytetracycline and 200 mg/kg Nosiheptide as positive control (PC), and basal diet plus 500 mg/kg compound probiotics consisting of heat-inactivated Bacillus subtilis and Lactobacillus acidophilus BFI (BFI). Each group had 6 replicates of 20 chickens. On d 21, 42, and 63, one chick from each replicate was selected for blood collection and cecal sampling. Compared to the NC group, dietary supplementation with heat-inactivated compound probiotics increased the feed efficiency during d 1-63 (P < 0.05). The plasma cholesterol content at 42 d and creatinine content at 63 d were decreased by dietary supplementation with heat-inactivated compound probiotics (P < 0.05). The dominant phyla in broiler cecal microbiota were Bacteroidetes, Firmicutes, and Proteobacteria, while the dominant genera were Bacteroides, Ruminococcaceae, and Phascolarctobacterium. The β-diversity index of cecal microbiota in BFI group was increased at d 42 (P < 0.01) and d 63 (P < 0.05). Dietary heat-inactivated compound probiotics increased the relative abundances of Barnesiellaceae (family), Barnesiella (genus), and Lactobacillus aviarius (species) at d 21, and reduced the relative abundances of genera Lachnoclostridium and Peptococcus at d 42, and unidentified Lachnospiraceae and Lachnoclostridium at d 63. The functional prediction of microbiota revealed that supplementation with heat-inactivated compound probiotics enriched the pathways related to methane metabolism, transcription machinery, purine metabolism and protein export. The Spearman's correlation analysis identified a significant correlation between cecal microbiota composition and overall feed efficiency and plasma metabolites. Collectively, dietary heat-inactivated compound probiotics with Bacillus subtilis and Lactobacillus acidophilus BFI enhanced feed efficiency, and decreased plasma cholesterol and creatinine contents, which might be associated with the modulation of community composition, diversity and functions of cecal microbiota in yellow-feathered broilers. These results indicated the potential of heat-inactivated probiotics used as alternatives to antibiotics for improvement of broiler health and productivity.This study was carried out to investigate the effect of heat-inactivated compound probiotics on growth performance, plasma biochemical indices, and gut microbiota composition and functions in yellow-feathered broilers. A total of 360 1-day-old broilers were randomly divided into 3 groups, including a basal diet as negative control group (PC), basal diet plus antibiotics with 250 mg/kg calcium oxytetracycline and 200 mg/kg Nosiheptide as positive control (PC), and basal diet plus 500 mg/kg compound probiotics consisting of heat-inactivated Bacillus subtilis and Lactobacillus acidophilus BFI (BFI). Each group had 6 replicates of 20 chickens. On d 21, 42, and 63, one chick from each replicate was selected for blood collection and cecal sampling. Compared to the NC group, dietary supplementation with heat-inactivated compound probiotics increased the feed efficiency during d 1-63 (P < 0.05). The plasma cholesterol content at 42 d and creatinine content at 63 d were decreased by dietary supplementation with heat-inactivated compound probiotics (P < 0.05). The dominant phyla in broiler cecal microbiota were Bacteroidetes, Firmicutes, and Proteobacteria, while the dominant genera were Bacteroides, Ruminococcaceae, and Phascolarctobacterium. The β-diversity index of cecal microbiota in BFI group was increased at d 42 (P < 0.01) and d 63 (P < 0.05). Dietary heat-inactivated compound probiotics increased the relative abundances of Barnesiellaceae (family), Barnesiella (genus), and Lactobacillus aviarius (species) at d 21, and reduced the relative abundances of genera Lachnoclostridium and Peptococcus at d 42, and unidentified Lachnospiraceae and Lachnoclostridium at d 63. The functional prediction of microbiota revealed that supplementation with heat-inactivated compound probiotics enriched the pathways related to methane metabolism, transcription machinery, purine metabolism and protein export. The Spearman's correlation analysis identified a significant correlation between cecal microbiota composition and overall feed efficiency and plasma metabolites. Collectively, dietary heat-inactivated compound probiotics with Bacillus subtilis and Lactobacillus acidophilus BFI enhanced feed efficiency, and decreased plasma cholesterol and creatinine contents, which might be associated with the modulation of community composition, diversity and functions of cecal microbiota in yellow-feathered broilers. These results indicated the potential of heat-inactivated probiotics used as alternatives to antibiotics for improvement of broiler health and productivity.